Keefektifan Program Pembinaan Kepala Sekolah Dasar dalam Era Pendidikan Dasar 9 Tahun - Suparno Suparno (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Effectiveness of Development Program for the Elementary School Principals in the Nine-Year Compulsory Education Era. The aim of the research was to know the success of elementary school principals in their supervision program. The population was all elementary school principals in the district of Sitiung, Sawahlunto Sijunjung, West Sumatra. A questionnaire was used to collect data, which were then analyzed statistically by percentages. The result revealed that 36 % of the elementary school principals were moderately effective, 60 % were highly effective and 4 % were very highly effective in their job as administrators. In addition, 28% of them were moderately effective, 32 % were highly effective and 40% were highest effective in their job as instructional supervisors.